EXPLORING TEACHERS’ EXPERIENCES IN IMPLEMENTING VISUAL LITERACY-BASED LEARNING MEDIA IN EARLY ELEMENTARY WRITING LESSON: A CASE STUDY - Turmudli; Sumarno; Achmad Buchori (SOSIOEDUKASI, 2025)
This study explores teachers' experiences in implementing visual literacy-based learning media in early elementary writing lessons. The purpose is to examine the impact of these media on student motivation, writing engagement, and learning outcomes. Using a qualitative case study approach, the research was conducted in a second-grade classroom, where teachers integrated visual literacy into writing instruction. The findings indicate that visual literacy-based media significantly enhanced students’ motivation and engagement in writing activities. Teachers reported that the media facilitated active participation and improved students’ ability to organize ideas and express thoughts through writing. The study concludes that visual literacy-based learning media is an effective tool for fostering creativity, critical thinking, and communication skills, contributing to a more interactive and engaging writing experience for young learners.